Fragilities and potentialities in the training of nurse leaders - Simone Coelho Amestoy; Letícia de Lima Trindade; Gilberto Tadeu Reis da Silva; Maria Manuela Martins; Patrícia Alves Galhardo Varanda; Ises Adriana Reis dos Santos (Universidade Federal do Rio Grande do Sul, 2021)
ABSTRACT Objective To know the perception of nursing professors about the fragilities and potentialities in the training of nurse leaders. Method Multiple case study, with a qualitative approach, performed with 36 nursing professors from a public university in the State of Bahia, Brazil. Data were collected through semi-structured interviews, interpreted in the light of Paulo Freire's theoretical framework and analyzed according to Thematic Analysis and the Nvivo®11 software. Results Were highlighted as fragilities the need to improve the transversality of leadership throughout graduation and teaching focused on the banking model. The potentialities refer to the insertion of the students in the practice scenarios, enabling the approximation with the nursing and multidisciplinary teams, the use of active methodologies and participation in research groups. Final considerations Professors consider the importance of problematizing pedagogical practices and invest in methodological strategies capable of promoting the training of nurse leaders.